The relative effectiveness of eribulin for advanced breast cancer treatment: a study of the southeast Netherlands advanced breast cancer registry. (2nd January 2020) - Pouwels, X. G. L. V.; Geurts, S. M. E.; Ramaekers, B. L. T.; Erdkamp, F.; Vriens, B. E. P. J.; Aaldering, K. N. A.; van de Wouw, A. J.; Dercksen, M. W.; Smilde, T. J.; Peters, N. A. J. B.; Riel, J. M. van; Pepels, M. J.; et al.
Abstract: Background: Eribulin provided significant overall survival (OS) benefit in heavily pretreated advanced breast cancer patients in the EMBRACE trial. We investigated the use of eribulin in daily clinical practice, the relative effectiveness of eribulin versus non-eribulin chemotherapy, and the safety of eribulin in real-world patients included in the SOutheast Netherlands Advanced BREast cancer (SONABRE) registry. Material and methods: Patients treated with eribulin and eligible patients for eribulin who received a different chemotherapy (i.e., non-eribulin group) in ten hospitals in 2013–2017 were included. A multivariate matching algorithm was applied to correct for differences in baseline characteristics between the groups, including the number of previous treatment lines. Progression-free survival (PFS) and OS of eribulin were compared with the matched non-eribulin group through Kaplan-Meier curves and multivariate Cox proportional hazard models. The occurrence of dose delay and reduction was described. Results: Forty-five patients received eribulin according to its registration criteria and 74 patients were eligible for eribulin but received non-eribulin chemotherapy. Matching increased the similarity in baseline characteristics between the eribulin and non-eribulin groups. Median PFS was 3.5 months (95% confidence interval (CI): 2.7–5.5) in the eribulin group and 3.2 months (95% CI: 2.0–4.8) in the matched non-eribulin group (adjusted hazard ratio (HR): 0.83, 95% CI: 0.49–1.38). Median OS was 5.9 months (95% CI: 4.6–11.0) and 5.2 months (95% CI: 4.6–9.5) in the eribulin and non-eribulin groups, respectively (adjusted HR: 0.66, 95% CI: 0.38–1.13). Dose delay or reduction occurred in 14 patients (31%) receiving eribulin. Conclusions: No difference in PFS and OS was observed between eribulin and non-eribulin treated patients. Eribulin had a manageable toxicity profile.